Measurement of Steroid Concentrations in Brain Tissue: Methodological Considerations - Taves, Matthew D.; Ma, Chunqi; Heimovics, Sarah A.; Saldanha, Colin J.; Soma, Kiran K. (Frontiers in Endocrinology, 2011)
It is well recognized that steroids are synthesized de novo in the brain (neurosteroids). In addition, steroids circulating in the blood enter the brain. Steroids play numerous roles in the brain, such as influencing neural development, behavior, neuroplasticity, and inflammation. In order to understand the regulation and functions of steroids in the brain, it is important to directly measure steroid concentrations in brain tissue. In this brief review, we discuss methods for the detection and quantification of steroids in the brain. We concisely present the major advantages and disadvantages of different technical approaches at various experimental stages: euthanasia, tissue collection, steroid extraction, steroid separation, and steroid measurement. We discuss, among other topics, the potential effects of anesthesia and saline perfusion prior to tissue collection; microdissection via Palkovits punch; solid phase extraction; chromatographic separation of steroids; and immunoassays and mass spectrometry for steroid quantification, particularly the use of mass spectrometry for “steroid profiling.” Finally, we discuss the interpretation of local steroid concentrations, such as comparing steroid levels in brain tissue with those in the circulation (plasma vs. whole blood samples; total vs. free steroid levels). This brief review highlights some of the major methodological considerations at multiple experimental stages and provides a broad framework for designing studies that examine local steroid levels in the brain as well as other tissues.